Pengaruh Teori Bruner terhadap Komunikasi Matematis Volume Kubus dan Balok di Kelas V SD - R, Yolanda; Ahmad, Syafri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
This research is aimed to find the effect of  application of Bruner theory on mathematical communication ability of students on the volume of cubes and blocks in class V SDN Cluster II District Lubuk Kilangan. Quantitative research with Quasi-Experimental method that uses a nonequivalent control group design. The sampling technique type of probability sampling cluster sampling type. The research sample that learners VB class at SDN 09 Bandar Buat as control class and a class VB at SDN 01 Bandar Buat as experiment class. The instrument used was multiple choice objective test with the reasons. Data were analyzed using t-test after normality and homogeneity test. The results showed that there are significant application of the theory of Bruner on mathematical communication skills on the volume of cubes and blocks of primary school. As evidenced obtained tcount (3.839) > ttable (2.002). So, there are significant differences in the results of mathematical communication in classes that implement the theory of Bruner with a class that implements the conventional teaching